Apport de différentes sources de données à la description comparée des contraintes et à l’amélioration d’un groupe de postes occupés en rotation - Anne Falardeau; Nicole Vézina (Perspectives Interdisciplinaires sur le Travail et la Santé)
An ergonomic intervention took place in a pig slaughterhouse and processing plant. This study consisted of analyzing and comparing a group of eight workstations occupied in rotation, in order to propose work organization and a refitting of the workstations for the purpose of reducing the constraints associated with each workstation and of optimizing the benefit to be drawn from rotation. To compare the workstations, different methodological tools (interviews, observations, self-confrontations) were used, including a questionnaire with scales of comparison for 13 parameters (learning, work pace, space, knives, body segments) was prepared and 19 evisceration workers answered it. The recommendations were developed from a survey, group meetings and tests. The results show that rotation within the group of workstations studied may allow a distribution of the constraints to the different body segments during the working day. Difficulties related to learning at these workstations and their relationships to the work place were also identified. Several recommendations were proposed regarding the refitting of the workstations and work organization.